CREAM current research in Malaysia = penyelidikan terkini di Malaysia - Malaysia. Kementerian Pengajian Tinggi (CREAM, 2012)
CREAM is published quarterly by the Ministry of Higher Education, Malaysia (four issues a year). It contains articles on Social Sciences and Humanities, ICT, Technology and Engineering, Pure and Applied Science and Health and Clinical Science. The primary purpose of this journal is to act as a channel for the publication of research work undertaken under various Ministry of Higher Education research grants.